Archaizing and Modernizing Strategies in Translation of the Texts in the 16-17th Centuries - Andrienko, Tetiana (East European Journal of Psycholinguistics, 2016)
The article explores the strategies of rendering temporal distance in translation of classical texts of Shakespearian times. Archaizing, modernizing and neutralizing strategies are studied at language (stylistic), cognitive and pragmatic levels. Archaizing strategy lies in creating an image of a bygone epoch using archaic lexemes and grammar forms, literal rendering of cognitive scenarios and pragmatic formulas. Modernization is creating an image of modern time as part of chronotope of the integrative text concept, by selecting contemporary counterparts, sometimes with colloquial or vulgar stylistic characteristics, replacing the archaic cognitive scenarios and pragmatic formulas with modern ones. The strategy of neutralizing the temporal distance means eliminating time-markedness from the image of the artistic work.ReferencesBaryshnikov, P. (2010). Metaphorical cognition and actualization of archaic concepts in thedaily discourse. Journal of International Scientific Publication: Language, Individual &Society, 4(1), 152–159 Bassnett, S. (2002). Translation Studies, 3rd ed. New York and London: Routledge,2002.Eco, U. (2000). Experiences in Translation. (A. McEwen, Trans.). University of TorontoPress.Hoyle R. A. (2008). Scenarios, Discourse, and Translation: The Scenario Theory of CognitiveLinguistics, Its Relevance for Analysing New Testament Greek and Modern Parkari Texts, andIts Implications for Translation Theory. Dallas: SIL International.Izard, C. E. (1991). The Psychology of Emotions. New York: Plenum Press.Jakobson R. (2000). On linguistic aspects of translation (1959) In: The TranslationStudies Reader. (pp. 114-118)., L. Venuti, M. Baker, (Eds.). Routledge London and NewYork.Jones, F. R., & Turner, A. (2004). Archaisation, Modernisation and Reference in theTranslation of Older Texts. Across Languages and Cultures, 5(2), 159–185.Kharmandar, M. A. (2014). Exploring archaism in translation theory and modern Persianpoetics: towards a Persian translation paradigm. Iranian Journal of Translation Studies, 12(46),40–56.Lefere, R. (1994). La traduction archaïsante: cervantes d’Après M. Molho. Meta, 39(1), 241–249.Malkki, A. (2009). Translating Emotions Across Time: Lewis Carroll’s Alice’s Adventures inWonderland. The Electronic Journal of the Department of English at the University ofHelsinki, 5. Retrieved from: http://blogs.helsinki.fi/hes-eng/volumes/volume-5/ translatingemotions-across-time-lewis-carroll’s-alice’s-adventures-in-wonderland-aila-malkki/MacDonald, P. S. Palaeo-Philosophy: Complex and Concept in Archaic Patterns of Thought /MacDonald, Paul S. In Cosmos and History: The Journal of Natural and Social Philosophy.Retrieved from: https://www.questia.com/read/1G1-170414880/palaeo-philosophy-complexand-concept-in-archaicMcElhanon, K. A. (2005). From word to scenario: the influence of linguistic theories uponmodels of translation. Journal of Translation, 1(3). 29–67.Steiner, G. (1998). After Babel: Aspects of language and translation, 3rd ed. London andOxford: Oxford University Press.Schleiermacher F. (1992). On the different methods of translating In: Translation.History. Culture: A Sourcebook (pp. 141–166). tr. and ed. A. Lefevere. London, NewYork: Routledge.Venuti, L. (1995). The Translator’s Invisibility: A History of Translation. London and NewYork: Routledge.